Bolstering cholesteryl ester hydrolysis in liver: A hepatocyte-targeting gene delivery strategy for potential alleviation of atherosclerosis. (June 2017) - He, Hongliang; Lancina, Michael G.; Wang, Jing; Korzun, William J.; Yang, Hu; Ghosh, Shobha
Abstract: Current atherosclerosis treatment strategies primarily focus on limiting further cholesteryl esters (CE) accumulation by reducing endogenous synthesis of cholesterol in the liver. No therapy is currently available to enhance the removal of CE, a crucial step to reduce the burden of the existing disease. Given the central role of hepatic cholesteryl ester hydrolase (CEH) in the intrahepatic hydrolysis of CE and subsequent removal of the resulting free cholesterol (FC), in this work, we applied galactose-functionalized polyamidoamine (PAMAM) dendrimer generation 5 (Gal-G5) for hepatocyte-specific delivery of CEH expression vector. The data presented herein show the increased specific uptake of Gal-G5/CEH expression vector complexes (simply Gal-G5/CEH) by hepatocytes in vitro and in vivo . Furthermore, the upregulated CEH expression in the hepatocytes significantly enhanced the intracellular hydrolysis of high density lipoprotein-associated CE (HDL-CE) and subsequent conversion/secretion of hydrolyzed FC as bile acids (BA). The increased CEH expression in the liver significantly increased the flux of HDL-CE to biliary as well as fecal FC and BA. Meanwhile, Gal-G5 did not induce hepatic or renal toxicity. It was also not immunotoxic. Because of these encouraging pre-clinical testing results, using this safe and highly efficient hepatocyte-specific gene delivery platform to enhance the hepatic processes involved in cholesterol elimination is a promising strategy for the alleviation of atherosclerosis.